CMET-38. IMPACT ON THE CLINICAL COURSE OF EGFR MUTATION ON BRAIN METASTASES FROM NON-SMALL-CELL LUNG CANCER FROM VIEWPOINT OF NEURO-ONCOLOGISTS. (5th November 2018) - Fujita, Yuya; Kinoshita, Manabu; Ozaki, Tomohiko; Takano, Koji; Kunimasa, Kei; Kimura, Madoka; Inoue, Takako; Tamiya, Motohiro; Nishino, Kazumi; Kumagai, Toru; Imamura, Fumio
Abstract: OBJECTIVE: Molecular and genetic alternations of non-small-cell lung cancer (NSCLC) now plays an important role in patient care of this neoplasm. The authors focused on the impact of EGFR mutation status on brain metastases (BM) from NSCLC to better understand the most desirable management of BM from NSCLC. METHODS: This was a retrospective observational study analyzing 266 patients with BM from NSCLC diagnosed between January 2008 and December 2015 in our institute. EGFR mutation, overall survival (OS), durations from diagnosis to brain metastases, and related factors with OS were measured. RESULTS: Among 266 patients, 127 patients (47.7%) had EGFR mutations. EGFR-mutant (EGFR-mt), compared with EGFR wild-type (EGFR-wt), showed longer median OS from diagnosis (40 vs 21 months, P < 0.001) and after BM diagnosis (22 vs 11 months, P < 0.001) and higher frequency of BM, around 80% of which occurred within 2 years. Good prognostic factors for OS were positive EGFR mutation (Hazard Ratio (HR) 0.64), no BM at diagnosis (HR 0.56), and single brain metastasis (HR 0.65). Patients harboring EGFR-mt single brain metastasis showed longer OS and durations from 1st brain metastasis to 2nd brain metastases than patients with either multiple BM or EGFR-wt BM. For those without BM at diagnosis, EGFR mutation status did not have any impact on OS (40 for EGFR-mt vs 37 months for EGFR-wt). CONCLUSIONS: Our study is in agreement with other studies that EGFR mutation is associated with prognosis of patients with BM from NSCLC. Results of our study also suggest that careful observation or screening for BM is recommended especially with the first 2 years for NSCLC patients with EGFR mutation. Aggressive treatments for EGFR-mt NSCLC patients with single BM should be considered taking into account that these patients could show prolonged survival after BM.